Comparison of left atrial lesion size and troponin release of two novel single shot devices for pulmonary vein isolation: pulsed field ablation vs. multi-electrode radiofrequency balloon. (19th May 2022) - Lemoine, M; My, I; Mencke, C; Butt, M; Schleberger, R; Muenkler, P; Rottner, L; Moser, F; Moser, J; Dinshaw, L; Reissmann, B; Ouyang, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Pulsed-field ablation (PFA) and the multi‐electrode radiofrequency balloon (RFB) are two novel ablation technologies to perform pulmonary vein isolation (PVI). It is currently unknown whether these technologies differ in lesion formation and lesion extent. Purpose: We compared the acute lesion extent after PVI induced by PFA and RFB by measuring low-voltage area in high-density maps and the release of biomolecules reflecting cardiac injury. Methods: PVI was performed with a pentaspline catheter (FARAPULSE) applying PFA or with the compliant multi‐electrode radiofrequency balloon (HELIOSTAR). Before and after PVI high-density mapping with CARTO3 was performed. In addition, blood samples were taken before transseptal puncture and after post-PVI remapping. Serum concentrations of high-sensitive Troponin I (hsTropI) were quantified by Immunoassay. Results: 50 patients undergoing PVI by PFA (n=26, age 71±10 y, 58% males, 58% persistent AF) or RFB (n=24; age 64±13 y, 54% males, 25% persistent AF) were evaluated. Acute PVI was achieved in all patients in both groups. Mean number of PFA pulses were n=34±5 and mean number RFB applications were n=8±3. Total posterior ablation area was bigger in PFA (19.0±6.2 cm²) than in RFB (9.0±2.2 cm²; p<0.001). The posterior distance between septal and lateral lesions was shorter in PFA (23.7±10.5 mm) than in RFB (30.0±7.3 mm; p=0.021). In a total of 38 patients increase of hsTropI was higher after PFA (625±138 pg/ml, n=28) vs. RFB (148±36 pg/ml; n=10; p=0.049) supporting the evidence of larger lesion extent by PFA. Conclusion: Pulse-field ablation delivers larger acute lesion areas and higher troponin release upon successful pulmonary vein isolation than multi-electrode array balloon-based pulmonary vein isolation in this single-center series.